Colour Doppler ultrasound hemodynamic characteristics of patients with priapism before and after therapeutic interventions - Chiou, Rei K. (Canadian Medical Association, 2009)
BACKGROUND: Information in the literature on the hemodynamic characteristics of priapism, especially after therapeutic intervention, is very limited. We analyzed our colour Doppler ultrasound (CDU) studies performed for patients with various durations of priapism before and after therapeutic intervention. METHODS: We reviewed 52 CDU studies for 24 patients with priapism before and after treatment for the period 1997–2007. The duration of priapism ranged from 4 hours to 8 days. We performed 17 CDU studies in 8 patients who presented with a duration of priapism of 7 hours or less, 9 studies in 4 patients who presented with duration of priapism of more than 20 hours, 23 studies in 11 patients referred to us after they had failed prior therapeutic intervention at other institutions and 3 studies in 1 patient with priapism related to perineal trauma. RESULTS: Among the 8 patients who presented with a duration of priapism of 7 hours or less, CDU studies on presentation showed detectible cavernosal arterial flow in all except 1 study. Among the 4 patients who presented with a duration of more than 20 hours, the studies showed no detectible cavernosal arterial blood flow. We repeated CDU studies after therapeutic intervention, and they showed restoration of cavernosal arterial flow with relief of veno-occlusive status. Among the 11 patients in whom prior treatments failed before they were referred to us, CDU studies performed on presentation showed no detectible cavernosal arterial flow in 10 of the 11 patients. We performed 12 CDU studies in 8 patients after placing a penile cavernosa-dorsal vein (CD) shunt. We observed the presence of blood flow in the CD shunt, indicating its patency in all 8 patients. Some patients showed high cavernosal arterial flow (peak systolic velocity [PSV] up to 27.6 cm/s) after surgery. These patients appeared to have residual priapism of primarily arteriogenic status that improved after observation. CONCLUSION: After therapeutic intervention, CDU study is useful to assess the relief of arteriogenic and veno-occlusive status and the decision for further treatment.